2012
DOI: 10.1177/0954410012469764
|View full text |Cite
|
Sign up to set email alerts
|

Airflow hazard prediction for helicopter flight in icing condition

Abstract: A methodology to predict the airflow hazard of helicopter flight in icing conditions is developed. By incorporating the existent ice accretion codes into an established basic helicopter flight dynamic model and considering airflow disturbance that mainly covers downdraft, head/tail wind, and left/right wind, the hazardous effects on trims, stability, and controllability of UH-60A single rotor helicopter in icing/ice-free conditions and within/without different types of wind field are investigated. The stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In addition, this deviation directly causes the difference in the aircraft position and orientation in its subsequent flight even after Figure 34. Longitudinal and lateral/directional dynamic responses of UH-60A helicopter to winds at different directions (177) .…”
Section: Flight Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this deviation directly causes the difference in the aircraft position and orientation in its subsequent flight even after Figure 34. Longitudinal and lateral/directional dynamic responses of UH-60A helicopter to winds at different directions (177) .…”
Section: Flight Dynamicsmentioning
confidence: 99%
“…One group of the current authors, Cao et al investigated the influence of wind shear on both helicopter flight characteristics (176,177) . It was found that left wind, tail wind and downdraft decrease the longitudinal stability, while the left wind, right wind and downdraft decrease the lateral/directional stability, as shown in Fig.…”
Section: Flight Dynamicsmentioning
confidence: 99%
“…The acoustic power of the tones was not measured but was considerable: the model could be heard two buildings over during use. 32 The data in the zero to three minute range shows pre-loading prior to the initiation of the test. The H23 sample was noted to be well attached, with the operator noting that the manual application of approximately 20 lbf normal force was required to separate the ice from the coupon post-test.…”
Section: First Irt Test Entry Data and Resultsmentioning
confidence: 99%
“…The run conditions for these tests are shown in APPENDIX A, and images of the XT model after a glaze ice spray during the third test are shown inFigure 73, which was similar to run conditions during the first test 32. This was anticipated during the design process; suitable countermeasures could not be identified.…”
mentioning
confidence: 90%
See 1 more Smart Citation